Echocardiographic Evaluation of Pulmonary Haemodynamics - A Review (Cardiovascular Journal, 2021)
Pulmonary haemodynamic status has got significant clinical and prognostic significance both in structural and nonstructural heart diseases. But diagnostic accuracy depends on much care in evaluation and logical correlation of different echocardiographic parameters. Though the Doppler studies play crucial role in estimating Pulmonary haemodynamics, careful observation of 2-D measurements of different structures as well as RV systolic and diastolic function are vital issues to be addressed and correlated for diagnostic accuracy. Tricuspid Valve, RVOT and Pulmonary valve pathologies also demand vivid correlation while estimating PA pressures and pulmonary vascular resistance. Mere presence of elevated pulmonary artery systolic pressure is not enough to define pulmonary hypertension (PH). Before declaring a patient having PH a comprehensive evaluation of right heart haemodynamics is to be performed carefully to avoid unnecessary cardiac catheterization or to avoid inadvertent initiation of PH therapy.Cardiovasc. j. 2021; 13(2): 200-216